2021
DOI: 10.4236/wjm.2021.114006
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Flow Behavior in Basilar Bifurcation Aneurysms Based on 4-Dimensional Computed Tomography Angiography

Abstract: Initiation, growth, and rupture of cerebral aneurysms are caused by hemodynamic factors. It is extensively accepted that the cerebral aneurysm wall is assumed to be rigid using computational fluid dynamics (CFD). Furthermore, fluid-structure interactions have been recently applied for simulation of an elastic cerebral aneurysm model. Herein, we examined cerebral aneurysm hemodynamics in a realistic moving boundary deformation model based on 4-dimensional computed tomographic angiography (4D-CTA) obtained by hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…In addition, the oscillatory shear index (OSI) and relative residence time (RRT) are hemodynamic stress parameters additional to WSS and WSSG [24]. It has been reported that the maximum values of OSI and RRT are both more sensitive than WSS [25,26]. Therefore, we considered that the same tendency can be seen in this study.…”
Section: Wall Shear Stressmentioning
confidence: 52%
See 1 more Smart Citation
“…In addition, the oscillatory shear index (OSI) and relative residence time (RRT) are hemodynamic stress parameters additional to WSS and WSSG [24]. It has been reported that the maximum values of OSI and RRT are both more sensitive than WSS [25,26]. Therefore, we considered that the same tendency can be seen in this study.…”
Section: Wall Shear Stressmentioning
confidence: 52%
“…Therefore, we considered that the same tendency can be seen in this study. However, because the shape of the cerebral aneurysm in this study differs from those of Yamazaki et al [25] and Abdollahi et al [26], there is a possibility that the trends in the sensitivity of RRT and OSI relative to WSS do not match. Therefore, the calculation of OSI and RRT is a future task.…”
Section: Wall Shear Stressmentioning
confidence: 57%